Dialectics of the Urgency of Reforming The Law of State Administrative Justice as a Synthesis - M Ikbar Andi Endang; Moh Fadli; Istislam Istislam; Dewi Cahyandari (Jurnal Dinamika Hukum, 2022)
Dialectically, previously the handling and settlement of state administrative disputes used Law Number 5 of 1986 concerning the Administrative Court Law which was twice revised with Law Number 9 of 2004 and Law Number 51 of 2009 as the legal instrument of the procedure ( thesis). However, currently, the procedural law used in resolving state administrative and government administrative disputes also uses the Supreme Court Regulation instrument. This is because the Administrative Court Law Law cannot accommodate the development of material administrative law requirements and administrative law enforcement provided by sectoral laws. Apart from that, in practice, there have been changes and shifts in most of the content of procedural law (material and formal) in the Administrative Court Law. This shift was influenced by the enactment of Law Number 30 of 2014 concerning Government Administration and sectoral laws which later became the basis for the formation of a Supreme Court Regulation. The two regulations later became guidelines for proceedings in the Administrative Court Law which had a paradoxical relationship. In one aspect, there is an interrelation between the law on Administrative Court Laws, the law on government administration, and the regulations of the Supreme Court, but in other aspects, it creates an antinomy of norms. Therefore, it is important in legal reform to encourage systematic thinking to synchronize and harmonize the material and formal content of the material and formal procedural laws that are unified as a synthesis.Keywords: dialectics, harmonization of law, shifting, state administration judicial procedural law